Value Added Tax on Home Purchases by Individuals - Silviu Cornel Chiriac (Agora International Journal of Economical Sciences (AIJES), 2022)
Starting from next year, the current system regarding value added tax for home purchases made by individuals will change. The change is made on the value ceilings of the transactions as well as on the number of transactions that can be carried out with the reduced VAT rate. The work aims to highlight the changes brought by the Government Emergency Ordinance no. 16 from 2022.
Keywords: 330